Construction and immunogenicity of an mRNA vaccine against chikungunya virus - Liu, Jingjing; Lu, Xishan; Li, Xingxing; Huang, Weijin; Fang, Enyue; Li, Wenjuan; Liu, Xiaohui; Liu, Minglei; Li, Jia; Li, Ming; Zhang, Zelun; Song, Haifeng; et al. (Frontiers in Immunology, 2023)
Chikungunya fever (CHIKF) has spread to more than one hundred countries worldwide, with frequent outbreaks in Europe and the Americas in recent years. Despite the relatively low lethality of infection, patients can suffer from long-term sequelae. Until now, no available vaccines have been approved for use; however, increasing attention is being paid to the development of vaccines against chikungunya virus (CHIKV), and the World Health Organization has included vaccine development in the initial blueprint deliverables. Here, we developed an mRNA vaccine using the nucleotide sequence encoding structural proteins of CHIKV. The results showed that the encoded proteins elicited high levels of neutralizing antibody titers and T cell-mediated cellular immune responses in mice. Moreover, compared to the wild-type vaccine, the codon-optimized vaccine elicited robust CD8+ T-cell responses and mild neutralizing antibody titers. In addition, higher levels of neutralizing antibody titers and T-cell immune responses were obtained using a homologous booster mRNA vaccine regimen of three different homologous or heterologous booster immunization strategies. Thus, this study provides assessment data for developing vaccine candidates and exploring the effectiveness of the prime-boost approach.